EFEKTIVITAS TEKNIK ANALISIS MANAJEMEN DALAM EVALUASI PROGRAM PENDIDIKAN ISLAM - Yanti Yulianti; Agus Karjuni; Feri Herdiana (Universitas Islam Bunga Bangsa Cirebon, 2022)
The evaluation of Islamic education programs is frequently conducted in a partial, reactive, and insufficiently data-driven manner, resulting in outcomes that have yet to promote systemic and sustainable program improvement. This condition reflects the suboptimal utilization of available management analysis techniques within the discipline of program evaluation. This study aims to explore, describe, and analyze the effectiveness of various management analysis techniques applied in the process of Islamic education program evaluation at several selected institutions. The method employed is qualitative with a multiple case study design, involving three Islamic educational institutions with differing characteristics as units of analysis. Data were collected through in-depth interviews, observation, and document review, then analyzed using coding-based thematic analysis techniques. The findings indicate that management analysis techniques such as the balanced scorecard, logic model, gap analysis, data-driven SWOT, and cost-effectiveness analysis demonstrate varying degrees of effectiveness depending on institutional readiness, human resource capacity, and the evaluative culture that has developed within each institution. The findings further reveal that the integration of Islamic values at every stage of evaluation is capable of enhancing the acceptance and commitment of practitioners toward evaluation outcomes. The integrative evaluation model formulated positions spirituality as an additional dimension that enriches the conventional management analysis framework.